PERAN BALAI PERMASYARAKATAN (BAPAS) KELAS 1 JAKARTA BARAT DALAM PELAKSANAAN PEMBINAAN DI LUAR LEMBAGA TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUMM(ABH) - Agata Ascourlina Mourin; Hery Firmansyah (Jurnal Hukum Adigama, 2019)
Juvenile delinquency is a criminal case which is caused by a child. Child convicted has to pass through the Juvenile delinquency system. In Indonesia, our Juvenile system gave some of the alternative criminal punishment beside imprisonment. The alternative criminal punistment are admonition, superision from authorized institution, establishment of child character outside or inside the institutions, work training, become a sosial worker and the last choice is prison punishtment. The best sanction is the one that can make the perpetrator know that the things he/she made are wrong and change their deed became behave well. In this case, author wants to discuss more about establishment of child character outside the institution who was handled by institution of government called Balai Permasyarakatan (BAPAS).